Best European fiction 2010 - Hemon, Aleksandar, 1964- (Champaign [Ill.] : Dalkey Archive Press, 2010)
Collects thirty-five short stories by both established and lesser-known authors from thirty European countries, including Antonio Fian, Alasdair Gray, and Victor Pelevin.
Includes bibliographical references (p. 401-414).
Booklist starred
Library Journal
Publisher's Weekly
Booklist starred, December 2009
Library Journal, November 2009
Keywords: Short stories, European; Short stories